Movement pattern comparisons in elite (AFL) and sub-elite (WAFL) Australian football games using GPS - Brewer, C.; Dawson, B.; Heasman, J.; Stewart, G.; Cormack, S. (Journal of Science and Medicine in Sport, 2010)
This study examined differences in movement patterns between AFL (elite) and WAFL (sub-elite) players using Global Positioning System (GPS) devices. Maximum speed data and totals of high intensity efforts (>15 km h-1), sprint efforts (>20 km h-1) and distance covered were collected on 41 players during the 2008 season. Data were expressed per min of game time played, separated into first and second halves, and also into positions, for both elite and sub-elite players. Overall, elite players had higher movement demands, including 9% more distance covered/min (128 ± 12 m min-1 vs. 117 ± 15 m min-1; p < 0.01, ES = 0.84), and 21% more high intensity efforts/min (2.9 ± 0.6 vs. 2.4 ± 0.6; p < 0.01, ES = 0.83). Movement demands significantly declined (p < 0.05-0.01) from first to second half, in both competition levels. For both leagues, Small Forwards/Small Backs and Midfield players covered significantly greater (p < 0.05-0.01) total distances and completed more high intensity efforts than other positions. Ruckmen recorded significantly lower (p < 0.05-0.01) movement demands than Small Forwards/Small Backs, Midfielders and Centre Half-Forwards/Centre Half-Backs over most variables. In conclusion, elite players recorded higher overall movement demands than sub-elite players. This information may be useful for coaches and conditioning staff in designing appropriate training drills for specific role requirements of individual players and assist in the progression of players from sub-elite to elite levels of competition.